A case report of bilateral primary cysts of paranasal sinuses - Usui, Nobuo; Kurotaki, Tosiaki; Miyazaki, Yukiko; Yuasa, Takafumi (JOURNAL OF JAPAN SOCIETY FOR HEAD AND NECK SURGERY, 2000)
The case report of the patient with what is called primary paranasal cyst, who had no history of nasal operation or facial injury was rare. Still more, the case of bilateral primary paranasal cysts was much rare. The patient was 74 years old female, and had the symptom of left nasal obstruction and diplopia. She underwent the operation of endoscopic sinus surgery. The histological finding of the cysts contained nasal gland, fibrous tissue, venous plexus, and chronic inflammatory cells infiltration in the submucosa. These findings corresponded to that of chronic sinusitis. At the surface of the mucosa there was squamous stratified epitherium or no epitherial component. As the existence of chronic inflammatory cells, ciliary epitherium might have degenerated to squamous epitherium. Furthermore there is no dental relative finding on the cysts' wall, both of these cysts were considered to be primary cysts.